International Symposium on Advancing Geodesy in a Changing World : Proceedings of the IAG Scientific Assembly, Kobe, Japan, July 30 -- August 4, 2017 /: Proceedings of the IAG Scientific Assembly, Kobe, Japan, July 30 -- August 4, 2017. (2019) - Unknown
No abstract available